2015
DOI: 10.1177/0956462415575424
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing behaviour and use of risk reduction strategies by HIV risk category among MSM in Vancouver

Abstract: We carried out an analysis of a serobehavioural study of men who have sex with men >19 years of age in Vancouver, Canada to examine HIV testing behaviour and use of risk reduction strategies by HIV risk category, as defined by routinely gathered clinical data. We restricted our analysis to those who self-identified as HIV-negative, completed a questionnaire, and provided a dried blood spot sample. Of 842 participants, 365 (43.3%) were categorised as lower-risk, 245 (29.1%) as medium-risk and 232 (27.6%) as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Echoing recent Dutch research, 5 we cannot tell whether viral load is being discussed with HIV-negative casual partners before sex without condoms or whether it is being "unilaterally" used by HIVpositive men. However, similar to Canadian research, 15 we found that 1 in ten HIV-negative and untested men frequently made sure that their HIV-positive partners had an undetectable viral load before sex without condoms. This suggests a growing awareness of "treatment as prevention" among Australian men who have sex without condoms, despite community skepticism about the concept.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Echoing recent Dutch research, 5 we cannot tell whether viral load is being discussed with HIV-negative casual partners before sex without condoms or whether it is being "unilaterally" used by HIVpositive men. However, similar to Canadian research, 15 we found that 1 in ten HIV-negative and untested men frequently made sure that their HIV-positive partners had an undetectable viral load before sex without condoms. This suggests a growing awareness of "treatment as prevention" among Australian men who have sex without condoms, despite community skepticism about the concept.…”
Section: Discussionsupporting
confidence: 87%
“…6,7 If consistently applied or sustained, condom use, an undetectable viral load and PrEP can be highly effective in preventing HIV infection, whereas the other strategies are generally less effective. 6,[8][9][10][11][12] The relative frequency of use of different strategies has been described among Australian, Swiss, and North American gay and bisexual men, 1,[13][14][15] suggesting that over three-quarters use some form of risk reduction during anal intercourse. In many countries, the most common RRS between casual partners remains condom use, with minorities reporting serosorting, strategic positioning, and withdrawal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this tool can be employed for sentinel behavioral surveillance. Data from the U.S., Australia and Canada suggest that partner viral load and PrEP use may impact sexual decision-making among MSM 1214 , but the trends in these behaviors have not been routinely monitored. Use of a brief behavioral assessment in the same population over time will help to understand what behaviors these newer ones (i.e., behaviors while on PrEP) are replacing and may also help explain changes in population-level HIV and STI rates.…”
Section: Discussionmentioning
confidence: 99%
“…A program of this type has been implemented by the Montpellier teaching hospital since 2013 in all addiction treatment centers located in the Languedoc Roussillon Region (Accueillir, 2014). Sex workers (Shokoohi et al, 2016), homeless people (Foroughi et al, 2017), migrants and some men who have sex with men (MSM) (Bogowicz et al, 2016), as well as populations living in hard to reach areas such as French Guiana (Schaub, 2017) are also key populations that can have difficult access to laboratory infectious diseases testing for which the use of DBS should be considered.…”
Section: Indications Of Dbs In Infectious Diseasesmentioning
confidence: 99%